Examining the Relationship Between Basic Psychological Needs and Athlete Identity During the COVID-19 Pandemic - Parker, Patti C.; Beeby, Adam M.; Daniels, Lia M. (Frontiers in Sports and Active Living, 2022)
Objectives During COVID-19 athletes have had games canceled, seasons postponed, and social supports lost. These changes negatively impact their motivation, and potentially identity, as athletes. We draw on self-determination theory to examine motivation in sport and its relationship with athlete identity during COVID-19. Design A cross-sectional study design was employed consisting of online quantitative surveys. Method We gathered background engagement and motivation data from 115 athletes involved in organized sport. They responded to questions on basic psychological needs satisfaction (competence, relatedness, autonomy) and athlete identity. Results When reflecting on their basic psychological needs during the pandemic, most athletes considered them important. Athletes' competence and relatedness in sport were associated with social-related athlete identity, but not autonomy. Only relatedness in sport was associated with exclusivity-related social identity. Conclusions Using a self-determination theoretical lens, our findings contribute to understanding athlete motivation and identities when sport is interrupted.